Colonizing the American continent: systematics of the genus arabis in North America (Brassicaceae) - Koch, Marcus; Karl, Robert; Kiefer, Christiane (American journal of botany, 2010)
The circumscription of the genus Arabis underwent many and drastic changes within the past. Using DNA sequence information from the nuclear ribosomal RNA and parts of the plastid genome (trnL-trnLF), as well as a critical evaluation of herbarium material from East Asia and North America, we circumscribe the various Arabis taxa of North America. The American and East Asian Arabis species are closely related and, contrary to what was previously believed, they are not closely related to the Eurasian A. hirsuta. Using cpDNA, we found five North American lineages of Arabis with distinct distribution patterns, of which only the purple/red-flowered lineage consists of proven diploids that evolved directly from East Asian progenitors. All other four lineages evolved via ancient hybridization either on the Asian continent prior to migration to North America or showed significant evidence for hybridization and reticulation while diversifying on the American continent. We also provide the first evidence for the systematic circumscription of East Asian Arabis taxa, which together with the North American taxa, form one clade distantly related to European A. ciliata and Eurasian A. hirsuta. The findings also represent the first record of A. pycnocarpa for the floras of China, Japan, and Russian Far East.
Gesehen am 09.05.2017